Comparing the trend of changes in oxygen pulse (RH/VO2) during maximal exercise after severe and moderate warming in women basketball players - Maryam Hosseını; Mansoureh Karımı; Hamid Agha-alınezhad (Türk Spor ve Egzersiz Dergisi)
As an indicator that carries oxygen through the circulatory system, oxygen pulse has recently been considered in clinical and exercise studies. There is no a lot of information about performance of the cardiovascular evaluator index. This study aims to compare trends of oxygen pulse (VO² / RH) during maximal exercise after moderate and severe warming in women basketball players. For this purpose, there were purposely selected seven women basketball players among players of basketball teams in League 1 of Tehran with average age of 21±1.52 years old, mean height of 166.8±3.72 cm, weighing average of 60.85±5.76 kg, body mass index of 21.71±1.72 kg/m2 and peak VO2 of 44.1±3.40 mL/kg/min with average of 6 years’ experience in basketball. After seven minutes of stretching exercises, each subject performed two warm up protocols before maximum exercise on two different days with 72 hours pause. The indicators of oxygen volume and oxygen pulse were measured using the device of breath-to-breath analysis. The research results showed that oxygen pulse during maximum exercise after intense warming has higher significant average than mean warming in times 0, 3 and 6. Accordingly, coaches should note that athletes should choose one of warm-up levels based on their physical fitness.